2003
DOI: 10.1300/j039v07n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Does PTSD Differ According to Gender Among Military Veterans?

Abstract: This was a study involving systematic random samples of 225 male and 232 female military veterans respectively that had received services at a VAMC in the South. The purpose was to examine what ecological factors predict a diagnosis of PTSD among those veterans. As expected, gender differences in relevant predictors of PTSD were observed: Generally, interpersonal factors, depression and fearfulness were more important to PTSD among women. Among men, self-efficacy, resilience, suicidal thoughts, alcohol and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The majority of reviewed studies (including research targeting combat trauma) enrolled both men and women. Some cross-sectional studies indicated that gender may moderate the relationship between self-efficacy and addiction-related or mental health outcomes (Benda & House, 2003). In contrast, longitudinal research suggests that gender may play a negligible role in explaining relationships between self-efficacy and health (Benight & Harper, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reviewed studies (including research targeting combat trauma) enrolled both men and women. Some cross-sectional studies indicated that gender may moderate the relationship between self-efficacy and addiction-related or mental health outcomes (Benda & House, 2003). In contrast, longitudinal research suggests that gender may play a negligible role in explaining relationships between self-efficacy and health (Benight & Harper, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Dobie et al (2004) reported a 36% prevalence of PTSD in a sample of female veterans as measured by the PCL. Benda and House (2003) found 40% of female veterans in their sample scored in the PTSD range on the Clinician-Administered PTSD Scale. Many of the women in our study who had experienced sexual assault in the military indicated a probable diagnosis of PTSD, including over half of pre-9/11 veterans and two thirds of post-9/11 veterans.…”
Section: Discussionmentioning
confidence: 97%
“…Even when sought, treatment within or outside the VA system may be unavailable, especially in rural and underserved geographic areas. In VA and private sector clinics alike, gender bias may limit diagnosis of PTSD in female veterans, especially those not exposed to direct combat (Benda & House, 2003; Pereira, 2002); VA disability policies may complicate diagnosis and treatment (Frueh, Grubaugh, Elhai, & Buckley, 2007; Spoont, Sayer, Nelson, & Nugent, 2007), or existing VA resources, like many community mental health resources, simply may be overwhelmed. Recently, the Office of the Assistant Secretary of Defense (Health Affairs) surveyed civilian mental health providers to determine where the private sector might fill the gap (T.V.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Pereira (2002) found that male veterans received a PTSD diagnosis 3.4 times more often than female veterans even though the females evidenced more PTSD symptoms than the males. Among 225 male and 232 female veterans receiving treatment at a VA Medical Center, only 19.8% of the 40.1% of women who met criteria for PTSD were actually diagnosed, while 59.1% of the 62.7% of men who met criteria for PTSD received the diagnosis (Benda & House, 2003). While combat injury in both men and women almost guaranteed PTSD claim approval (90%), women who developed PTSD symptoms from a sexual assault during their military service were far less likely to receive a PTSD diagnosis (Murdoch et al., 2003).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
See 1 more Smart Citation